Relationship between Stress Levels and Eating with Hypertension in the the Baji Dakka Treatment Room at Labuang Baji Hospital in Makassar - Ratna; H. Ismail; Sri Wahyuni (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
Hypertension is established at systolic pressure of 140 mmHg / more when at rest, diastolic pressure of 90 mmHg / more when at rest or on the move. This study uses a cross sectional research method, the purpose of this study was to determine the relationship of stress levels and eating patterns with the incidence of hypertension in hospitalized patients in the Baji Dakka treatment room at Labuang Baji Hospital in Makassar. The method of sampling uses accidental sampling method, where data collection is done by interviewing, filling out questionnaires. Many factors can trigger hypertension, one of which is stress and diet. When a person experiences stress, the body will produce the hormone adrenaline which can increase blood pressure, and uncontrolled eating patterns lead to an increase in blood volume, so that the heart's work in pumping blood also increases and thickening of artery walls by fat or cholesterol (atherosclerosis) which including foods containing fat are organ meats, chicken eggs, coconut milk foods, and all foods processed with cooking oil. The number of samples 37 respondents. The collected data is processed and analyzed using a computer statistics program. Data analysis included univariate analysis by looking for frequency distribution, and bivariate analysis by chi-square test of significance α <= 0.05 to determine the relationship between stress and eating patterns on the incidence of hypertension. The results of the bivariate analysis showed a stress relationship p = 0,000 <α = 0.05 and dietary patterns p = 0,000 <α = 0.05.